Land Tenure Regimes and Women’s Land Rights in Uganda; Legality and the Land Legal Framework. - Kemigisha, Prudence (Advances in Social Sciences Research Journal, 2021)
A review on the implications of land tenure regimes on women’s land rights is relevant in the Ugandan context and other countries in Africa due to the fact that land is in many ways the most important productive resource to possess or have access to. Rights over land are associated with social identity and help to regulate what people do with that land as a source of livelihood. Despite the critical contribution of land resource, it is not equitably distributed. The position of women in land accessibility, control and ownership is still precarious under the different tenure regimes in Uganda. A literature review was conducted to assess the implications of the tenure regimes on women land rights in Uganda, with specific reference to the land legality and the legal framework. From the literature reviewed, the study indicates that women’s right to land under the land holding systems are largely limited to access rights but not ownership rights. Ugandan women face significant challenges accessing justice when their rights are violated. The lack of clear distinction between legitimacy and legality of land rights makes it difficult to attain effective women’s rights to land. A combination of contemporary and customary law still restricts land rights of women in that the statutory instruments in place have failed to grant women the right to land. The study recommends that the necessary change required to narrow the gender gap in land rights necessitates simultaneous struggles over the norms and legal structures governing women’s land rights.